Kinesioterapia en pacientes pediátricos quemados. - Sofía Alexandra (2022)
ABSTRAC The research was of a documentary type, carried out through a bibliographic review, with the aim of analyzing and highlighting the academic-scientific information on the effects of kinesiotherapy as part of the rehabilitation process of pediatric patients who have suffered burns to demonstrate the actions of physiotherapy. in this population. Burns are injuries to the skin or deeper tissues caused by the sun, hot liquids, fire, electricity or chemicals, being a cause of accidental morbidity and mortality in pediatric age; consequently, dermatofunctional physiotherapy intervenes with the application of kinesiotherapy as part of the rehabilitation treatment to improve the functional limitations caused by burns, through dosed movement and in correspondence to biomechanics and physiology. Academic information was collected from different databases such as Scielo, Dialnet, Pubmed, among others; Around 35 scientific articles published worldwide in both Spanish and English were validated and included; the Physiotherapy Evidence Database (PEDro) scale was applied as a methodological validation tool; in addition to the Scimago Journal impact factor and Ranking (SJR). The investigation concluded that kinesiology is important for pediatric burn patients, the same ones that present problems in their musculoskeletal system, showing in several bibliographic sources significant results on beneficial effects in improving strength, strengthening, mobility and functionality of each patient, managing to see improvement in the lifestyle of each patient. Keywords: physiotherapy, burns, pediatrics, skin, mobilization.